Effect of hormonal contraception on depression, anxiety and quality of life: A controlled study - de Souza, Flávia Cristina Barros; Aragão, Francisca Bruna Arruda; Brito, Luciane Maria Oliveira; Reis, Andréa Dias [UNESP]; de Oliveira Neto, Clariano Pires; da Costa Chein, Maria Bethânia (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2020)
Objective: Identify the effect of oral hormonal contraceptive use on depression, anxiety, and quality of life. Methods: A cross-sectional study method was used and the sample was 113 women on reproductive age. Depression, anxiety, and QoL were assessed by the BECK Inventory, the State-Trait IDATE, and the SF-36, respectively. For the statistical analysis, the STATA 14.0 program was used. The level of significance was 5%. Results: Women who use oral contraceptives have age 24,02 ± 5,30 years, menarche 12,23±1,40 years, and weight 58.9 kg. Nonconsumption of alcohol and tobacco prevailed, respectively, with 73 (64.60%) and 111 (98.23%). Concerning the use of combined oral hormonal contraceptives and without the use of COHC in relation to the type of anxiety and level of depression, there was no statistically significant difference between them. Asymptomatic women prevailed in relation to depression (without the use of combined oral hormonal contraceptives 61/82.43%) and presence of anxiety/trait and anxiety/status in both groups. QoL was not impaired by the use of combined oral hormonal contraceptives or not. Conclusion: Contraceptive use is not related to the presence of anxiety, depression, and quality of life alteration.
Efeito do contraceptivo hormonal na depressão, ansiedade e qualidade de vida: Estudo controlado
Keywords: Anxiety; Contraceptives; Depression; Quality of life